The tourist infrastructure of the waterway in a segment of the lower Warta River = Infrastruktura turystycznego szlaku wodnego na odcinku Dolnej Warty - Hudak, Magda; Paczkowska, Andżelika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Polish segment of the E70 International Waterway comprises an area stretching from the western border of Poland with Germany (the estuary of the Warta River) to Żuławy Wiślane (including the area surrounding the Polish part of the Vistula Lagoon). This waterway leads along the Warta River, the Noteć River, the Bydgoski Canal, the Brda River and the delta of the Vistula River.
Keywords: turystyka wodna; szlak wodny; infrastruktura turystyczna; Dolna Warta; water tourism; objects of infrastructure; Warta river